FROM REJECTION TO CONFRONTATION: A STUDY ON THE ONTOLOGICAL SECURITY PERSPECTIVE OF POLAND’S RELATIONS WITH RUSSIA - Yan, Ke (PEOPLE: International Journal of Social Sciences, 2024)
In the field of international security studies, attention to ontological security issues has become a focal point. Ontological security at the national level manifests as the dynamic harmony between “national super-ego” and “national Id”, representing a common product in the subject relations. Ontological security crisis is the result of the failure of “national ego” regulation. Positioned in the geopolitical periphery, Poland, over millennia, has developed a distinct “national super-ego” and a strong sense of identity. However, throughout its history, Poland has repeatedly faced ontological security challenges from Russia. For Poland, Russia has transformed from being the “other” to the “excluded”, ultimately becoming the “adversary” in Poland’s ontological security. Since the “post-Cold War” era, Poland has endeavored to reshape its ontological security through internal and external measures. Ontological security provides a novel perspective for international relations research.